Penerapan Metode Pembelajaran Demonstrasi pada Pelajaran IPS di SD - Nunia Namsa; Sukadari Sukadari (UM Purwokerto Press, 2023)
This research intends to identify how the application of demonstration teaching and learning methods is applied to social studies lessons in elementary schools. This study uses a research formulation that explorer social issues and will be thoroughly, broadly and deeply examined. Library research procedures are used for this type of research. With the method of gathering information from a variety of relevant library materials, including novels, diaries, posts and others related to the application of demonstration procedures in social studies lessons in elementary schools. The Application of the demonstration procedure was carried out in 2 steps, namely the planning step and the implementation step. Procedure demonstration of use is efficient because procedure demonstration encourages students become active in learning and this will also make the learning given in class seem more meaningful so that it makes it easier for students to understand and remember the lessons delivered by the teacher.